2002
DOI: 10.1016/s0895-7061(01)02251-8
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime blood pressure dipping: the role of the sympathetic nervous system

Abstract: There is a marked diurnal variation in blood pressure (BP), with BP dipping to its lowest levels during nighttime sleep. A day-night dip in systolic BP (SBP) of <10% has been used to characterize individuals as nondippers, and is associated with an increased risk for cardiovascular disease. The present study examined the contribution of the sympathetic nervous system (SNS) to BP dipping in a biracial sample of 172 men and women aged 25 to 45 years. Assessments included 24-h ambulatory BP monitoring and both wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
193
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(208 citation statements)
references
References 37 publications
10
193
2
3
Order By: Relevance
“…31 Nondippers with a Ͻ10% nocturnal decrease in systolic blood pressure compared with dippers showed a reduced fall during the night in the urinary excretion rate of catecholamines. 32 The above studies 31,32 might explain why our patients with isolated nocturnal hypertension had increased heart rates at night and suggest that an attenuated withdrawal of sympathetic drive during sleep might contribute to isolated nocturnal hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…31 Nondippers with a Ͻ10% nocturnal decrease in systolic blood pressure compared with dippers showed a reduced fall during the night in the urinary excretion rate of catecholamines. 32 The above studies 31,32 might explain why our patients with isolated nocturnal hypertension had increased heart rates at night and suggest that an attenuated withdrawal of sympathetic drive during sleep might contribute to isolated nocturnal hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…Although underlying mechanisms are still unknown, sympathetic over activity, functional and structural vascular alterations, early autonomic neuropathy have all been seen in patients with non-dipping BP (Hommel et al 1989;Sherwood et al 2002). Insulin resistance is the underlying mechanisms of both MS and hypertension (Modan et al 1985;Swislocki et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…24 Sherwood et al 25 showed that the night time fall in the excretion rate of both adrenaline and noradrenaline was reduced in nondippers compared to dippers. Non-dippers are characterized also by heightened responsiveness of a 1 adrenergic receptors.…”
Section: Discussionmentioning
confidence: 99%